1994
DOI: 10.1002/bjs.1800811124
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and postoperative demands on hospital and community services after day surgery

Abstract: This study presents the outcome of a survey of patients satisfaction following day surgery and an assessment of the level of contact between patients and community services within the first 48 h after discharge from a day-surgery unit. A total of 953 patients were provided with a self-completion questionnaire after day surgery; replies were received from 557 (58.4 per cent). Areas investigated regarding overall satisfaction were outpatient services, admission procedure, day-surgery services, preoperative and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 3 publications
4
39
0
1
Order By: Relevance
“…Firstly, issues concerning patient expectations. A large number of studies highlight the public's general satisfaction with, and preference for, day surgery (Clyne and Jamieson 1978, Jamison et al 1987, Harju 1991, O`Connor et al 1991, Buttery et al 1993, Fenton-Lee et al 1994, Ghosh and Sallam 1994, Gupta et al 1994, Sigurdardottir 1996, Lawrence et al 1997, Pollock and Trendholm 1997, Bhattacharya et al 1998, Willsher et al 1998. However, some aspects within day surgery were not always expected.…”
Section: Patients' Experiences In the Day Surgery Unitmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, issues concerning patient expectations. A large number of studies highlight the public's general satisfaction with, and preference for, day surgery (Clyne and Jamieson 1978, Jamison et al 1987, Harju 1991, O`Connor et al 1991, Buttery et al 1993, Fenton-Lee et al 1994, Ghosh and Sallam 1994, Gupta et al 1994, Sigurdardottir 1996, Lawrence et al 1997, Pollock and Trendholm 1997, Bhattacharya et al 1998, Willsher et al 1998. However, some aspects within day surgery were not always expected.…”
Section: Patients' Experiences In the Day Surgery Unitmentioning
confidence: 99%
“…Also, Nkyekyer (1996) reported 34% of patients found the wait prior to surgery too long and O'Connor et al (1991) also reported 11% found the wait too long. As a consequence both Ghosh and Sallam (1994) and Otte (1996) recommended staggered admission times on the day of surgery. Male (1981) and Wicklin and Forster (1994) concluded female patients together with patients undergoing local anaesthesia to be more anxious.…”
Section: Patients' Experiences In the Day Surgery Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain control also has great financial implications. Uncontrolled pain is a main reason for delayed discharge and unanticipated readmission [7,8]. As the Centers for Medicare and Medicaid's Hospital Readmissions Reductions Program, Physician Quality Reporting System (PQRS), and Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) results link patient outcomes and satisfaction to reimbursement, pain management is increasingly important [9][10][11].…”
mentioning
confidence: 99%
“…There are a number of descriptive studies, surveys and audits of satisfaction in day patients. 19,168,172,178,180,181,183,196 Telephone surveys to look at patient satisfaction with day-surgery services have also been carried out. 185 Clinical audits are common in day-case practice to assess patient satisfaction with overall services and consider improvements.…”
Section: Methods Usedmentioning
confidence: 99%